Prevalence of carbapenem resistance and its potential association with antimicrobial use in humans and animals in rural communities in Vietnam. Issue 2 (19th April 2022) - Yen, Nguyen Thi Phuong; Nhung, Nguyen Thi; Phu, Doan Hoang; Dung, Nguyen Thi Thuy; Van, Nguyen Thi Bich; Kiet, Bach Tuan; Hien, Vo Be; Larsson, Mattias; Olson, Linus; Campbell, James; Quynh, Nguyen Pham Nhu; Duy, Pham Thanh; et al.
Abstract: Background: Vietnam and Southeast Asia are hotspots for antimicrobial resistance; however, little is known on the prevalence of carriage of carbapenem resistance in non-hospitalized humans and in animals. Carbapenem-resistant Enterobacteriaceae (CRE), particularly Escherichia coli (CREC) and Klebsiella pneumoniae (CRKP) and also Acinetobacter baumannii (CRAB) are emerging threats worldwide. Methods: We investigated healthy humans ( n  = 652), chickens ( n  = 237), ducks ( n  = 150) and pigs ( n  = 143) in 400 small-scale farms in the Mekong Delta of Vietnam. Samples (rectal swabs, faecal swabs) were investigated for carriage of CRE/CRAB and were further characterized phenotypically and genotypically. Results: In the Mekong Delta of Vietnam, the prevalence of CRE isolates in human rectal swabs was 0.6%, including 4 CREC and 1 CRKP. One pig was infected with CREC (prevalence 0.7%). CRAB was isolated from chickens ( n  = 4) (prevalence 2.1%) and one duck (prevalence 0.7%). CRKP was isolated from a human who was also colonized with CREC. The CRKP strain (ST16), from an 80 year-old person with pneumonia under antimicrobial treatment, genetically clustered with clinical strains isolated in a hospital outbreak in southern Vietnam. The prevalence of CRE was higher among humans that had used antimicrobials within 90 days of the sampling date than those had not (4.2% versus 0.2%) ( P  = 0.005). All CRE/CRAB strains were MDR, although they were susceptible to colistin and neomycin. The carbapenemase genes identified in study strains were bla NDM and bla OXA . Conclusions: The finding of a CRKP strain clustering with previous hospital outbreak raises concerns about potential transmission of carbapenem-resistant organisms from hospital to community settings or vice-versa.